IMPLEMENTATION OF GUIDANCE AND COUNSELING IN OVERCOME LEARNING DIFFICULTIES IN EARLY CHILDHOOD - Ida Septiani Sari; Salsa Nurhaliza; Nurul Bayyinah (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2022)
The purpose of this study was to determine the efforts of supervising teachers in overcoming learning difficulties in early childhood. The object of this research is the supervising teacher from RA An-nur Jakarta. The number of participants involved was three participants. The data and research were collected by interview technique, then the data were analyzed by qualitative descriptive technique. After the data is collected and analyzed, it can be concluded that the efforts of the supervising teacher in overcoming learning difficulties in early childhood at RA An-nur are quite good. The results showed that the method used by the supervising teacher at RA An-nur to overcome learning difficulties in early childhood used Islamic counseling guidance methods, namely through example, for example providing motivation, educating with love and affection. Based on the research above, the authors suggest to the supervising teacher to increase creativity in teaching and learning efforts, have skills in diagnosing early childhood who have learning difficulties, and in carrying out services they should cooperate more with parents.